Ex vivo validation of magnetically actuated intravascular untethered robots in a clinical setting - Leendert-Jan W. Ligtenberg; Nicole C. A. Rabou; Constantinos Goulas; Wytze C. Duinmeijer; Frank R. Halfwerk; Jutta Arens; Roger Lomme; Veronika Magdanz; Anke Klingner; Emily A. M. Klein Rot; Colin H. E. Nijland; Dorothee Wasserberg; et al. (Communications Engineering)
Abstract Intravascular surgical instruments require precise navigation within narrow vessels, necessitating maximum flexibility, minimal diameter, and high degrees of freedom. Existing tools often lack control during insertion due to undesirable bending, limiting vessel accessibility and risking tissue damage. Next-generation instruments aim to develop hemocompatible untethered devices controlled by external magnetic forces. Achieving this goal remains complex due to testing and implementation challenges in clinical environments. Here we assess the operational effectiveness of hemocompatible untethered magnetic robots using an ex vivo porcine aorta model. The results demonstrate a linear decrease in the swimming speed of untethered magnetic robots as arterial blood flow increases, with the capability to navigate against a maximum arterial flow rate of 67 mL/min. The untethered magnetic robots effectively demonstrate locomotion in a difficult-to-access target site, navigating through the abdominal aorta and reaching the distal end of the renal artery.